Tubular adenoma arising in tubular colonic duplication: a case report - Heonwoo Lee; Hyeong Rok An; Chan Wook Kim; Young Soo Park (Korean Society of Pathologists & the Korean Society for Cytopathology, 2024)
Colonic duplication constitutes a rare congenital anomaly, characterized by the presence of hollow cystic or tubular structures exhibiting an epithelial-lined intestinal wall. Diagnostic challenges persist due to its low incidence and manifestation of nonspecific symptoms such as abdominal pain or constipation, resulting in a reluctance to pursue surgical resection. As associated malignancies in colonic duplication are rare, the inherent malignant potential of these anomalies remains undetermined. Additionally, despite reported instances of associated malignancies in colonic duplication, there is an absence of reports in the literature detailing tubular adenoma within these cases. The histologic features of the presented case are particularly noteworthy, situated at the precancerous stage, intimating potential progression towards adenocarcinoma within colonic duplication.